An introduction to Qur'anic sciences ('ulum al-Qur'an) - Jaffer, Abbas; Jaffer, Masuma (ICAS Press, 2009)
Studies of the Qur'anic sciences have either been partial, brief, or sectarian. In the main, such works have more or less ignored the contribution of the great Shia scholars to our understanding of the Qur'anic sciences. This book presents a fresh view of this important topic. It is of interest to undergraduate students who are studying Islam